IN VITRO EFFICACY OF CICLOPIROX AGAINST CARBAPENEM RESISTANT ENTEROBACTERIACEAE - Ansari, Maliha; Ikram, Hassan; Saad, Nadia; Hanif, Aaminah; Sadia, Aiza; Ullah, Qazi Ikram (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the in vitro efficacy of Ciclopirox against Carbapenem Resistant Enterobacteriaceae by determining its minimum inhibitory concentration by micro agar dilution method. Study Design: Quasi experimental study. Place and Duration of Study: The department of Microbiology, Army Medical College, Rawalpindi, National University of Sciences and Technology, Islamabad Pakistan, from Apr 2015 to Apr 2016. Methodology: Sample size 45 Carbapenem Resistant Enterobacteriaceae. Clinical specimens like naso-bronchial lavage (NBL), blood, pus, sputum, urine, body fluids and catheter tips, routinely received in the department of Microbiology, Army Medical College, Rawalpindi were subjected to standard microbiological methods. Enterobacteriaceae were identified by colony morphology, and API 20 E (Biomeriux. France). Carbapenem resistance was detected by using imipenem/meropenem discs (10ug) by modified Kirby bauer disc diffusion method. Ciclopirox minimum inhibitory concentration (MIC) against the selec-ted samples of Carbapenem resistant Enterobacteriaceae was measured using micro agar dilution protocol done in accordance with clinical laboratory standards institute (CLSI). Results: All 45 (100%) carbapenem resistant enterobacteriaceae (CRE) were sensitive to ciclopirox. Forty-three out of 45 (95.5%) of carbapenem resistant Enterobacteriaceae were multi drug resistant (MDR) i.e., sensitive only to minocycline, tigecycline, and colistin. Minimum inhibitory concentration of ciclopirox was determined against multi drug resistant Carbapenem resistant Enterobacteriaceae was found to be 25µg/ml. Two (4.44%) were pan drug resistant and the Minimum inhibitory concentration of ciclopirox for these organisms was 50 µg/ml. Conclusion: Ciclopirox is highly effective in vitro against Carbapenem resistant Enterobacteriaceae at Minimum inhibitory concentration between 25-50 µg/ml.